Socio-Economic HUBRIS / (SA(Bn Alternative Approach to Sovereign Debt Crisis Managements - Pappas John D; Research Institute For Legal And Economic Reform (2012)
This book lays out a (qualitative) model that is in line with the IMF's (quantitative) comprehensive balance sheet methodology for diagnosing macroeconomic vulnerabilities. Abstract, Contents, Introduction, Structure and Definitions, Sovereign Debt Trap, Leisure-Oriented Economy, Work-Oriented Economy, Totally Neutral Economy, Heterogenous Economy, Economic Emulation, Structural Rate of Net Growth, Adjustment Period, Structural Distribution, Socio-Economic Hedging, Totally Hedged Economy, Liberal Economy, Autonomous Economy without Measure, Motivational Expansion, Sovereign Debt Crisis Management, Wealth Redistribution, Unconditional Debt Reduction, Redistributive Debt Reduction, Motivational Contraction, Socio-Economic Blitz, Index.